The interaction between teacher educators and their students on the use of educational technology: Similarities and differences of attitudes, skills, and practice across a generational change - Thorvaldsen, Steinar; Madsen, Siri Sollied (European Association of Distance Teaching Universities, 2018)
Source at https://conference.eadtu.eu/download2468 . Norway has been exposed to a stronger top-down implementation of ICT in education than most other countries. The pervasive change in Norwegian school curriculum has consequently resulted in changes in Norwegian initial teacher education. National plans have emphasized digital competence as one of the basic competencies that teacher educators and student teachers are required to focus on during their initial teacher education. Teacher education has a double role in digitally rich classrooms; it develops both student teachers’ professional skills and the students’ ability to facilitate pupils’ learning. Despite the political effort, it seems that practitioners in the Norwegian education system are not working in line with the given policy, and it appears to be a gap between what is stated in the curricula and what practitioners are doing. This gap is often explained by practitioners’ deficiency and/or lack of interest. To understand these relations better, and to help us predict the future use of educational technology in our schools, we have conducted a quantitative comparative study between teacher educators in Northern Norway and their students (N=112). It appears from the analysis that among the staff the professional attitudes have a stronger impact than digital competence regarding the extent of educational use of digital tools, while digital competence has a stronger influence than attitudes among the students. These results are interpreted through Argyris & Schön’s Theory of Action .